Pacto resolutorio expreso algunos comentarios sobre su regulación civil y registral - Ortega Piana, Marco Antonio (2023)
In the event of a serious breach of obligations, and having lost interest in the due performance, the creditor, as a faithful party to the respective legal relationship, may choose to invoke the agreement that had been expressly agreed, thereby terminating the respective contract by the sole merit of the respective communication. Being the so-called express termination clause a figure that should not generate further discussion, the latter arises in relation to the content of the agreement and the manner of exercising the respective elective right. It is therefore appropriate to consider what the legislator intended within the framework of private autonomy, since the freedom of configuration must be exercised in correspondence with the rationality of the respective figure to be applied and the imperative rules, which is an insurmountable limit. The topic acquires singular relevance because the registry regulations allow a resolution derived from the exercise of the express resolutory agreement to be registered at the request of the interested party, of the creditor, specifically of the person who transferred the ownership of a real estate property through the registry, who reacquired such ownership, with an effectiveness that is not limited inter parties, but erga omnes.